THE FEASIBILITY ANALYSIS OF SEINE NET THE MOORING AT PORT OF BELAWAN NORTH SUMATRA PROVINCE - Esra Gerdalena; Zulkarnaini '; Hendrik ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research about the analysis of Seine net was conducted on March, 17 to 31, 2015 at the Port of Belawan North Sumatra Province. This research purpose is to know the amount of capital investments and feasibility of Seine net. The method used in this research is survey method by purposive random sampling to determination of the respondents that the crew, captain and ship owners 30 GT and 60 GT are mooring in the port of Belawan. The results of this research showed that investment of the Seine net 30 GT was Rp 738.175.000 and the Seine net 60 GT was Rp 954.550.000. Investment criteria for ship of the Seine net 30 GT the value of NPV was Rp 2.688.915.982, BCR was 1,40 dan IRR was 68,64%, while the Seine net of 60 GT the value of NPV was Rp 3.547.943.205, BCR was 1,42 dan IRR was 68,82%. This showed that the effort ship of Seine net 30 GT and 60 GT profitable and feasible to be continue.Keywords : Seine net, Feasibility, Port of Belawan.